Influence of Social Network on Language Use of Kejaman Speakers in Sarawak, Malaysia - Amee, Joan; Ting, Su Hie (Project MUSE, 2017)
The Kejaman are a small indigenous group living in the interior of Belaga in the Malaysian state of Sarawak. This preliminary study examines the influence of social network on the language use of Kejaman speakers. The study involves 30 Kejaman teenagers who had moved out of Belaga to continue their secondary education in a nearby town, Bintulu. Their ability to speak Kejaman varies, ranging from those who cannot speak Kejaman to those who can interact fluently in Kejaman. The density of their exchange network (M = 82.22 percent) is much higher than that of their interactive network (M = 50.00 percent). The low multiplexity score of 20.83 percent shows that the interaction among the Kejaman participants tends to be confined to one capacity or domain. The results show low usage of Kejaman in relation to other languages in the exchange and interactive networks (mean ratio of 0.39 and 0.30, respectively). There are no significant relationships between the density of their social network, the ability to speak Kejaman, and the use of Kejaman in relation to other languages. Established procedures of social network analysis were used, but the results showed that density and multiplexity can no longer be considered as cooccurring indicators of network ties because communication technologies have brought geographically distant network ties into frequent contact, and yet the geographical distance means that the ties are not multiplex. The findings suggest that the ethnic index of social networks may be more indicative of ethnic language maintenance or shift.